(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The development of eco-friendly carbon-free marine energy is actively underway to alleviate the impact of global climate change due to excessive emission of carbon dioxide. To reduce the variability of energy production according to marine environment conditions and maximize energy production, the need for research on a suitable ocean energy platform is increasing. Therefore, various studies on motion control of ocean energy platforms are being conducted. In this study, the motion response of a combined wind-wave energy platform equipped with multiple wave energy converters (WEC) capable of controlling the motion of a floating offshore wind turbine (FOWT) was numerically analysed and verified through a wave tank experiment. The combined energy platform with multiple WECs attached to the FOWT not only produces stable energy by controlling the motion response of the FOWT with the movement of the WEC, but also produces wave energy by the relative motion of the WEC. The FOWT is a spar platform with taut moorings, and WEC is a moving cylinder hinged to the FOWT. The motion reduction effect of the FOWT by the movement of the WEC was investigated. Numerical analysis used the ANSYS AQWA program, which is a potential flow-based hydrodynamic program. To consider the restraining force of the FOWT due to the motion of the WEC, the multi-body dynamics theory was applied. The accuracy of the numerical model was improved by applying mooring dynamics, weakly nonlinear Froude-Krylov force, and nonlinear hydrostatic force. The experimental model was fabricated on a scale of 1/100 of the numerical model and was performed in a two-dimensional mini wave tank. To prevent the sidewall effect of the tank, the experiment was conducted only for the incident waves with various periods under the head sea conditions. The numerical analysis results were in good agreement with the experimental results. In particular, the pitch of FOWT decreased significantly near the pitch resonance period because of the motion of WEC. The change in motion characteristics of the combined energy platform according to the movement of the WEC under various wave conditions was analysed.